Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! To show that [tex]\(\frac{1}{z} = \frac{\bar{z}}{|z|^2}\)[/tex] for a nonzero complex number [tex]\( z = a + bi \)[/tex], we will proceed with the following steps:
1. Step 1: Definition of Conjugate
The conjugate of a complex number [tex]\( z = a + bi \)[/tex] is given by:
[tex]\[ \bar{z} = a - bi \][/tex]
2. Step 2: Definition of Modulus and Modulus Squared
The modulus of [tex]\( z = a + bi \)[/tex] is:
[tex]\[ |z| = \sqrt{a^2 + b^2} \][/tex]
Therefore, the modulus squared is:
[tex]\[ |z|^2 = (a + bi)(a - bi) = a^2 + b^2 \][/tex]
3. Step 3: Finding the Multiplicative Inverse
To find [tex]\(\frac{1}{z}\)[/tex], we multiply both numerator and denominator by the conjugate of [tex]\( z \)[/tex]:
[tex]\[ \frac{1}{z} = \frac{1}{a + bi} \cdot \frac{a - bi}{a - bi} = \frac{a - bi}{(a + bi)(a - bi)} \][/tex]
Simplifying the denominator using the result from Step 2:
[tex]\[ \frac{1}{z} = \frac{a - bi}{a^2 + b^2} \][/tex]
4. Step 4: Expressing the Result
Notice that [tex]\( \bar{z} = a - bi \)[/tex] and [tex]\( |z|^2 = a^2 + b^2 \)[/tex]. Then:
[tex]\[ \frac{1}{z} = \frac{a - bi}{a^2 + b^2} = \frac{\bar{z}}{|z|^2} \][/tex]
Thus, we have shown that:
[tex]\[ \frac{1}{z} = \frac{\bar{z}}{|z|^2} \][/tex]
This completes the proof.
1. Step 1: Definition of Conjugate
The conjugate of a complex number [tex]\( z = a + bi \)[/tex] is given by:
[tex]\[ \bar{z} = a - bi \][/tex]
2. Step 2: Definition of Modulus and Modulus Squared
The modulus of [tex]\( z = a + bi \)[/tex] is:
[tex]\[ |z| = \sqrt{a^2 + b^2} \][/tex]
Therefore, the modulus squared is:
[tex]\[ |z|^2 = (a + bi)(a - bi) = a^2 + b^2 \][/tex]
3. Step 3: Finding the Multiplicative Inverse
To find [tex]\(\frac{1}{z}\)[/tex], we multiply both numerator and denominator by the conjugate of [tex]\( z \)[/tex]:
[tex]\[ \frac{1}{z} = \frac{1}{a + bi} \cdot \frac{a - bi}{a - bi} = \frac{a - bi}{(a + bi)(a - bi)} \][/tex]
Simplifying the denominator using the result from Step 2:
[tex]\[ \frac{1}{z} = \frac{a - bi}{a^2 + b^2} \][/tex]
4. Step 4: Expressing the Result
Notice that [tex]\( \bar{z} = a - bi \)[/tex] and [tex]\( |z|^2 = a^2 + b^2 \)[/tex]. Then:
[tex]\[ \frac{1}{z} = \frac{a - bi}{a^2 + b^2} = \frac{\bar{z}}{|z|^2} \][/tex]
Thus, we have shown that:
[tex]\[ \frac{1}{z} = \frac{\bar{z}}{|z|^2} \][/tex]
This completes the proof.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.